A new retrograde transillumination technique for videolaryngoscopic tracheal intubation. (18th January 2018) - Biro, P.; Fried, E.; Schlaepfer, M.; Kristensen, M. S.
Summary: This single‐centre, prospective trial was designed to assess the efficacy of a new retrograde transillumination device called the 'Infrared Red Intubation System' (IRRIS) to aid videolaryngoscopic tracheal intubation. We included 40 adult patients, who were undergoing elective urological surgery under general anaesthesia. We assessed the ability to differentiate the transilluminated glottis from other structures and found a median (IQR [range]) larynx recognition time of 8 (5–14 [3–28]) s. The difference in laryngeal visibility on the screen between the deactivated vs. activated device expressed on a visual analogue scale was significant (6 (4–7 [2–10]) vs. 10 (8–10 [4–10]); p < 0.001). The number of laryngoscope insertions was 1 (1–2 [1–3]) and the device showed high values on a visual analogue scale ranging from 0 (lowest score) to 10 (highest score) for helpfulness (6 (5–7 [2–10])), credibility (10 (8–10 [5–10])) and ease of use (10 (9–10 [8–10])). Tracheal intubation with the system lasted 26 (16–32 [6–89]) s. No alternative technique of securing the airway was necessary. The lowest SpO2 during intubation was 98 (97–99 [91–100])%. We conclude that this method of retrograde transillumination can assist videolaryngoscopy.